Relationship Level of Knowledge about Anemia with Compliance Consuming Fe Tablet in The Public Health Centre - Nia kurniawati; Endang Maryanti; Zuriati Muhamad (Hasanuddin Medan, 2022)
Due to their inability to meet their own iron requirements, mothers who are pregnant with iron deficiency are placing their unborn children at risk for birth defects such as low fatal organ maturity and prematurity. Hypovolemic hemorrhage during labour in anemic conditions increases the chance of death. Pregnant women's knowledge of anemia and their adherence to Fe pills in the Public Health Centre, Langkat Regency were the primary goals of this study. Cross-sectional surveys were used in this type of research. All pregnant women in the working area of Public Health Centre, Langkat Regency, were surveyed in August, with a total of 68 people participating. For this investigation, the method of sampling was total sampling. Results of the Study Regarding 67% of those polled have inadequate information about anemia, and 41% of those polled don't take their medication as directed (60.3%). Adherence to taking Fe pills is strongly influenced by a person's level of knowledge. The p-value is less than 0.05. Increasing pregnant women's knowledge of the importance of taking Fe pills is recommended in order to raise their degree of adherence to taking Fe tablets.